Change in Peel Color of Guava Fruit (Psidium guajava L.) ‘Crystals’ During Storage - Mufza, Haya Fadhila; Arti, Inti Mulyo; Pribadi, Edi Minaji; Miska, Moh Ega Elman (Jurnal Ilmu Pangan dan Hasil Pertanian, 2023)
The appearance of the fruit, especially in terms of appearance and color, is an essential assessment for consumers. The physical quality of guava can be seen from the visual appearance of the fruit peel through image data and quantitative color degrees. This study aimed to determine the effect of harvest age on the visual appearance and peel color changes of crystal guava and organoleptic values of crystal guava peel color during storage.The factor studied was harvest age at 90, 100, 110, and 120 days after anthesis (DAA). Parameters observed were visual appearance through image data, brightness level (L), and degree of reddish-bluish (a*) and greenish-yellowish (b*) and color organoleptic score for 9 days of storage at room temperature. The results showed that the peel of the guava fruit at the age of 90 DAA was bright green compared to the peel of the fruit at the old age of 120 DAA, which had a slightly yellowish-green color. The harvest age of guava fruit significantly affects the level of L, degrees a* and b* of crystal guava peel starting on day 7 of 9 days of storage. The results of the color organoleptic test values can be maintained up to a score of 6 on the 5th day and close to a score of 2 on the 8th day of storage.